Privatization of Education in India - swaranjali24, swaranjali24 (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2022)
Education is one of the fastest growing service sectors of the Indian economy. The medical and health care sector alone has developed faster than education sector. The Education Commission (1964-66) set down a total public expenditure on education of 6% per annum on GNP by 1986 if the national income increased at the rate of 6% per annum and population growth, at 2.1% per annum during (1955-56) to (1985-1986). Keywards: Indian economy, population growth, developed faster